Physico-chemical parameters measured at a high spatial resolution in the Miellajokka catchment, Sweden - Rocher-Ros, Gerard; Department of Ecology and Environmental Sciences, Umeå university (Umeå University, 2018)
High spatial resolution dataset of CO2 evasion in a stream network in northern Sweden (52.5 km2; Miellajokka catchment). We measured key hydrological parameters to estimate k600, directly determined the pCO2, and estimated stream CO2 evasion across 168 sites in the stream network. The publication of this data is currently ongoing. Please contact the main author for further details (g.rocher.ros@umu.se)

Dataset med hög rumlig upplösning för CO2-avflyttning i ett strömnätverk i norra Sverige (52,5 km2; Miellajokka upptag). Viktiga hydrologiska parametrar mätades för att uppskatta k600, direkt bestämd pCO2 och beräknad strömavlopp CO2-undvikning över 168 platser i strömnätet.
Fysikalisk-kemiska parametrar mätt vid en stor rumslig upplösning i Miellajokka-avrinningen, Sverige
Keywords: Hydrology; Hydrologi; DISSOLVED CO2; Natural landscapes; Naturlandskap; Natural Sciences; Naturvetenskap; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Biological Sciences; Biologi; Climatology / Meteorology / Atmosphere; Klimatologi och meteorologi; Environment; Miljö